Borrowed or Native Vision of Common History? The Influence of Byzantine Authors on the Historical Consciousness of South and East Slavs (Based on the Story of Muhammad and Peter of Sicily’s History of the Paulicians) (Phantom of Muhammad, Shade of Samuel Byzantine Empire in Relation to Members of Other Cultures and Religions (7th–15th c.): No. XXXIX, 2020)
In this article, the influence of Byzantine historiographic texts on Slavic ideas about infidels is presented (based on the example of Islam and dualistic heresy).